Mesenchymal Stem Cells in the Treatment of Traumatic Brain Injury - Hasan, Anwarul; Deeb, George; Rahal, Rahaf; Atwi, Khairallah; Mondello, Stefania; Marei, Hany Elsayed; Gali, Amr; Sleiman, Eliana (Frontiers in Neurology, 2017)
Traumatic brain injury (TBI) is characterized by a disruption in the normal function of the brain due to an injury following a trauma which can potentially cause severe physical, cognitive and emotional impairment. The primary insult to the brain initiates secondary injury cascades consisting of multiple complex biochemical responses of the brain that significantly influence the overall severity of the brain damage and clinical sequelae. The use of mesenchymal stem cells (MSCs) offers huge potential for application in the treatment of TBI. MSCs have immunosuppressive properties that reduce inflammation in injured tissue. As such, they could be used to modulate the secondary mechanisms of injury and halt the progression of the secondary insult in the brain after injury. Particularly, MSCs are capable of secreting growth factors that facilitate the regrowth of neurons in the brain. The relative abundance of harvest sources of MSCs also makes them particularly appealing. Recently, numerous studies have investigated the effects of infusion of MSCs into animal models of TBI. The results have shown significant improvement in the motor function of the damaged brain tissues. In this review, we summarize the recent advances in the application of MSCs in the treatment of TBI. The review starts with a brief introduction of the anatomy of the human brain and the pathophysiology of TBI, followed by the biology of MSCs, and the application of MSCs in TBI treatment. The challenges associated with the application of MSCs in the treatment of TBI and strategies to address those challenges in the future have also been discussed.